2016
DOI: 10.3892/ijo.2016.3394
|View full text |Cite
|
Sign up to set email alerts
|

Fibulin-5 downregulates Ki-67 and inhibits proliferation and invasion of breast cancer cells

Abstract: Abstract.Fibulins not only function as molecular bridges within the cellular microenvironment but also influence cell behavior. Thus, fibulins may contribute to create a permissive microenvironment for tumor growth but can also stimulate different mechanisms that may impede tumor progression. This is the case with Fibulin-5, which has been shown to display both tumor-promoting and tumor-protective functions by mechanisms that are not totally defined. We show new evidence on the tumor-protective functions displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Therefore, FBLN5 acts as a tumor suppressor in ovarian cancer. Similarly, FBLN5 over expression inhibited invasion and proliferation capacity of several breast cancer lines including MCF-7, T47D and MDA-MB-23148. Interestingly, FBLN5 also prevent these cells from forming mammospheres, a key feature of cancer stem cells48.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, FBLN5 acts as a tumor suppressor in ovarian cancer. Similarly, FBLN5 over expression inhibited invasion and proliferation capacity of several breast cancer lines including MCF-7, T47D and MDA-MB-23148. Interestingly, FBLN5 also prevent these cells from forming mammospheres, a key feature of cancer stem cells48.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, FBLN5 over expression inhibited invasion and proliferation capacity of several breast cancer lines including MCF-7, T47D and MDA-MB-23148. Interestingly, FBLN5 also prevent these cells from forming mammospheres, a key feature of cancer stem cells48. Thus, depending on tumor type, FBLN5 may either promote or inhibit tumor growth through mechanisms that are not totally understood.…”
Section: Discussionmentioning
confidence: 99%
“…Fbln5 is reported to promote cell proliferation or tumor growth in mouse 3T3-L1 fibroblasts or human HT1080 fibrosarcoma cells 25 , mouse pancreatic ductal adenocarcinoma 46 , and human gastric cancer MGC-803 cells 47 . On the other hand, several previous studies have demonstrated inhibition of cell proliferation by Fbln5 overexpression in mouse vascular smooth muscle cells 18 , human breast cancer cells 48 , mink lu Mv1Lu epithelial cells 25 , primary human saphenous vein endothelial cells 49 , and rat retinal pigment epithelial cells 50 . Thus, further investigation of the pathway that mediate Fbln5 action on β-cell proliferation is required.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, Fbln5 is reported to have context‐dependent oncogenic and tumor‐suppressing roles . Increased levels of Fbln5 reduce cell migration and invasion in ovarian and breast cancer .…”
Section: Resultsmentioning
confidence: 99%